(untitled) (European Journal of Marketing and Economics, 2018)
The human resource management is a basic function which affects the objectives achievement not only on business field, but also on the other spheres of the human activity. The purpose of this paper is to study the involvement and motivation of employees in the organization environment. In order to realize the purpose of this paper, we have analyzed the actual evaluation system of employees in the banking sector and the link among the motivation programs and the satisfaction in the work place. We have raised two hypotheses: H1: Employees of different hierarchical levels are satisfied with their current motivation programs, and H2: Both female and male employees think that the organization helps them balance their private life with their work life. The primary data are collected through a questionnaire. Hypotheses are tested using the Kolmogrov-Smirnoff test. We used SPSS for data analyzing. From the analyses it results that for some employees the immediate monetary rewards are more important, while for some others the relationship with colleagues and leaders, the work conditions, the work challenge and the opportunities for career growth are more important. We concluded that only male employees manage to balance their work live with private life. As a conclusion we can say that nowadays we need new motivation techniques, mainly for female employees, in order to create a balance among their personal life and their work life. We recommended new programs that can be implemented in business organizations, such as cultural activities, flexible working hours, entertainment activities during trainings and seminars, programs for how employees can better balance their personal life with their job, employee involvement in decision making, and motivation through improving communication and presentation skills.